2002
DOI: 10.1111/j.1349-7006.2002.tb02470.x
|View full text |Cite
|
Sign up to set email alerts
|

U‐shaped Effect of Drinking and Linear Effect of Smoking on Risk for Stomach Cancer in Japan

Abstract: A case-control study was conducted to evaluate the relationship between smoking or drinking doses and risk for stomach cancer, and to clarify whether the relationship is dose-dependent or U-shaped. Smoking dose was categorized as 0, 1-399, 400-799, or 800+ + + + cigarette-years, and drinking dose as 0, occasional/0.1-134.9, 135-1349.9, or 1350 + + + + alcohol-years (ml of pure alcohol intake per day multiplied by years of drinking). Helicobacter pylori status was determined by serology for adjustment. Using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
3
24
1
Order By: Relevance
“…11,18,19) Few studies have reported the sexspecific risk of stomach cancer. 23,25) The present results provide evidence indicating that Japanese male smokers are at an elevated risk of stomach cancer. Curiously, in females, on the other hand, smoking history was inversely associated with stomach cancer risk.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…11,18,19) Few studies have reported the sexspecific risk of stomach cancer. 23,25) The present results provide evidence indicating that Japanese male smokers are at an elevated risk of stomach cancer. Curiously, in females, on the other hand, smoking history was inversely associated with stomach cancer risk.…”
Section: Discussionsupporting
confidence: 59%
“…Otherwise, distributions of anatomical and histologic subtype among female stomach cancers may be related to the inverse association with cigarette smoking among females, since some previous studies have indicated that the association with cigarette smoking may differ in this way. 23,25) We could not clarify risk patterns by subtype due to incomplete data for subtype in our hospital cancer registry. Therefore, detailed analyses by anatomical and histologic subtype are needed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the risk grouping of patients with welldifferentiated gastric adenocarcinoma (at onset), the presence or absence of H. pylori infection (5,6), smoking history (18,19), history of alcohol consumption (19) and serum pepsinogen levels (4,6) have been reported as relevant. However, these factors have not been demonstrated to be useful for risk grouping poorly-differentiated gastric adenocarcinoma patients.…”
Section: Discussionmentioning
confidence: 99%